Factors associated with pain and osteoarthritis at the hip and knee in Great Britain's Olympians: a cross-sectional study. Issue 17 (14th May 2018) - Cooper, Dale J; Scammell, Brigitte E; Batt, Mark E; Palmer, Debbie
Abstract : Background: Knowledge of the epidemiology and potentially modifiable factors associated with musculoskeletal disease is an important first step in injury prevention among elite athletes. Aim: This study investigated the prevalence and factors associated with pain and osteoarthritis (OA) at the hip and knee in Great Britain's (GB) Olympians aged 40 and older. Methods: This is a cross-sectional study. A survey was distributed to 2742 GB Olympians living in 30 countries. Of the 714 (26.0%) who responded, 605 were eligible for analysis (ie, aged 40 and older). Results: The prevalence of hip and knee pain was 22.4% and 26.1%, and of hip and knee OA was 11.1% and 14.2%, respectively. Using a multivariable model, injury was associated with OA at the hip (adjusted OR (aOR) 10.85; 95% CI 3.80 to 30.96) and knee (aOR 4.92; 95% CI 2.58 to 9.38), and pain at the hip (aOR 5.55; 95% CI 1.83 to 16.86) and knee (aOR 2.65; 95% CI 1.57 to 4.46). Widespread pain was associated with pain at the hip (aOR 7.63; 95% CI 1.84 to 31.72) and knee (aOR 4.77; 95% CI 1.58 to 14.41). Older age, obesity, knee malalignment, comorbidities, hypermobility and weight-bearing exercise were associated with hip and knee OA and/or pain. Conclusions: This study detected an association between several factors and hip and knee pain/OA in retired GB Olympic athletes. These associations require further substantiation in retired athletes from other National Olympic Committees, and through comparison with the general population. Longitudinal follow-up is needed to investigate the factors associated with the onset and progression of OA/pain, and to determine if modulation of such factors can reduce the prevalence of pain and OA in this population.